(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Nutritionists and Dietitians are types of health workers in the group of nutrition workers in Indonesia. Nutritionists are nutritionists with nutrition education starting from Diploma III to Doctoral in Nutrition, while Dietitians are nutritionists who have graduated from Professional Dietitian Education. Currently TGM is given by Nutritionists and Dietitians, but in practice the boundaries of the roles of the two have not been determined according to the level of acuity. The acuity level indicates the amount of medical-related support needed for a patient and is measured through assessment. Nutritional acuity levels differ from medical ones. Escott-stump's nutritional acuity level was based on a survey of more than 100 dietitians. The ranking consists of 4 levels which describe the involvement of the Dietitian and the time of administration of TGM (MNT-Time). The ranking helps nutrition management improve service quality through staff planning, standardization of nutrition care, identification of inappropriate referrals, support for young staff and as a guideline for nutrition triage to determine priority of patients who must be treated immediately. Based on patient acuity, the American Dietetic Association in 2004 proposed a dietitian: patient ratio of 1:65 – 1:75 (internal medicine services) and 1:30 – 1:60 (ICU services). The Canadian Dietitian Association compiled a nutrition care priority matrix consisting of 3 levels namely high, medium, low based on nutritional risk, patient condition, role of nutrition, SGA, MST, and time frame. The level of nutritional acuity needs to be developed in Indonesia to map the role of nutritionists and dietitians in providing TGM so that optimal nutrition care outcomes are achieved, reducing costs for malnourished patients and providing quality services.